Co3O4@Co/NCNT Nanostructure Derived from a Dicyanamide Based Metal-Organic Framework as Efficient Bi-functional Electrocatalyst for Oxygen Reduction and Evolution Reactions - Sikdar, Nivedita; Konkena, Bharathi; Masa, Justus; Schuhmann, Wolfgang (Chemistry–A European Journal, 2017)
There has been growing interest in the synthesis of efficient reversible oxygen electrodes for both the oxygen reduction reaction (ORR) and the oxygen evolution reactions (OER), for their potential use in a variety of renewable energy technologies, such as regenerative fuel cells and metal-air batteries. Here, a bi-functional electrocatalyst, derived from a novel dicyanamide based nitrogen rich MOF {[Co(bpe)2(N(CN)2)]⋅(N(CN)2)⋅(5 H2O)}n [Co-MOF-1, bpe=1,2-bis(4-pyridyl)ethane, N(CN)2−=dicyanamide] under different pyrolysis conditions is reported. Pyrolysis of the Co-MOF-1 under Ar atmosphere (at 800 °C) yielded a Co nanoparticle-embedded N-doped carbon nanotube matrix (Co/NCNT-Ar) while pyrolysis under a reductive H2/Ar atmosphere (at 800 °C) and further mild calcination yielded Co3O4@Co core–shell nanoparticle-encapsulated N-doped carbon nanotubes (Co3O4@Co/NCNT). Both catalysts show bi-functional activity towards ORR and OER, however, the core–shell Co3O4@Co/NCNT nanostructure exhibited superior electrocatalytic activity for both the ORR with a potential of 0.88 V at a current density of −1 mA cm−2 and the OER with a potential of 1.61 V at 10 mA cm−2, which is competitive with the most active bi-functional catalysts reported previously.